Variables of repetition and procrastination in students of Logic and algorithms I and II at the University/Variables generadoras de la repitencia y procrastrinación en estudiantes de Lógica y algoritmos I y II en la Universidad de la Amazonia (Encuentros, 2019)
The objective of this work is to identify the main variables that generate difficulties in the learning of undergraduate students in Logic and Algorithms I and II in the Faculty of Engineering of the University of Amazonia. The research was carried out through a case study approach and a descriptive analysis of the presented situation, evaluating the competences of autonomous learning through surveys. In this sense, in developing the work, a diagnosis was established to generate strategies and take action on the partof the academic directivesKey words: repetition; autonomous learning competences; educational development competences.